FAKTOR-FAKTOR YANG MEMENGARUHI LUARAN THERAPEUTIC PLASMA EXCHANGE PADA KRISIS MIASTENIA DI RSUPN CIPTO MANGUNKUSUMO - Manfaluthy Hakim; Triana Ayuningtyas; Ahmad Yanuar; Nadia Ayu Mulansari; Winnugroho Wiratman; Luh Ari Indrawati; Astri Budikayanti; Fitri Octaviana (NEURONA, 2021)
Introduction: Myasthenic crisis (MC) occurs due to worsening symptoms of myasthenia gravis (MG) characterized by acute respiratory failure, prolonged post-thymectomy intubation or bulbar weakness causing dyspnoea. Therapeutic Plasma Exchange (TPE) has been accepted as first-line therapy for MC. The management of TPE is not quite ideal according to the American Society of Apheresis (ASFA) recommendations. Aim: To determine the factors that in????uenced the outcomes of MC patients who underwent TPE Methods: This study was a cross-sectional design by taking secondary data on MC cases that received TPE at RSUPN Cipto Mangunkusumo from January 2014 to September 2018. The diagnosis of MC is based on clinical examination. Bivariate analysis was carried out on factors that infuenced TPE outcomes in MC. Results: A total of 38 cases met the inclusion criteria. Good outcomes after undergoing TPE are found in 60.5% of cases. The onset of MG (p=0.039) and type of MG (p= 0.001) have a significant relationship with TPE outcome on MC. Early-onset MG and ocular to generalized MG show good outcomes. Antibody specificity variables showed a strong trend in infuencing TPE outcome in MC (p=0.055). Patients with MC who underwent TPE according to ASFA showed faster clinical improvement than those who underwent TPE not according to ASFA. Discussion: Early-onset MG and ocular to generalized MG are factors that can affect the excellent outcome of TPE in MC. Patients who undergo TPE, according to ASFA, show faster clinical improvement. Keywords: ASFA, myasthenic crisis, therapeutic plasma exchange